(3GdEYQGH Yf bhGYO GdEYQGHs - (3YHO Gddg Hf jhSa Hf CMeO Hf YHO Gddg Hf jhSa GdCfUGQj GdeUQj GdfMhj , LeGd GdOjf , CHh eMeO, J (B761 (3g` s
(3ChdgG (B:s
(3bGd GdTjN LeGd GdOjf Hf eMeO Hf gTGe gPg ahGFO LdjdI ai bhGYO GdEYQGH hSejJgG HGdEYQGH Yf bhGYO GdEYQGH hJfMUQ ai CQHYI CHhGH GdHGH GdChd ai GdLedI hTQMgG hajg CQHY eSGFd s
(3BNQgG (B:s
(3hcKjQ ef GdeJbOejf jSehf GdRGFO Udg hHYVge jSejg eDcOkG hai gPG GdbOQ caGjh def JCedg s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH (B3s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3eUOQ GbJfGA GdCUd (B:s
(3GdRGhjI GdMeRGhjI (B_ (3GdeZQH (B(190) s
Keywords: (3GdeLGejYs